Effect of using some treating exercises for the calf muscle post-effort and its effect on the achievement of the triple jump for the second stage students - Jameel Hussein Al-Saadi, Israa; Muhammad Abdulkhaliq Alhasan, Ahmed; Razzaq Jawad, Baydaa (International Journal of Psychosocial Rehabilitation, 2020)
We Cannot reach high sports results depending on the increase in the volume and intensity of training only, and without concomitant operations of hospitalization to get rid of the fatigue caused by carrying the impact of training and the goal of developing motor levels of performance and achievement in various sports skills and to address the means to test that develop achievement in effectively Triple jump: One of these means is hospitalization exercises, as the rapid progress that has been made to achieve the high achievement in triple jump in the present time and the development of many specialized researches as well as therapeutic and hospitalization methods to reduce pressure on the body as well as medical means to reduce injuries and keep the player Therefore, the researchers conducted the post-tests and then applied the hospitalization exercises in a manner appropriate to the age group and the size of the injury, and then the post-tests were conducted in the same conditions as the tribal tests on the research sample